2018
DOI: 10.24815/cdj.v10i2.11710
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Tingkat Kepuasan Estetik Dan Fonetik Pada Pemakai Gigi Tiruan Lengkap Di Fakultas Kedokteran Gigi Universitas Trisakti

Abstract: Kehilangan seluruh gigi merupakan masalah kesehatan yang diderita oleh kebanyakan lansia. Jika masalah ini tidak diperbaiki akan mengganggu kecantikan (estetik) dan gangguan bicara (fonetik) pada pasien lansia. Untuk mengatasi masalah ini pasien dibuatkan gigi tiruan lengkap (GTL). Pasien lansia memiliki beragam tingkat kepuasan tergantung dari hasil pelayanan yang diberikan dan GTL yang dibuatkan. Penelitian ini adalah untuk mengetahui tingkat kepuasan pasien dalam menggunakan gigi tiruan lengkap dari segi es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This study's results align with Shigli et al (2007) where people are more motivated to use dentures to restore chewing than for esthetics and speech function. Because someone who loses teeth in the front will feel insecure in their environment, whereas someone who loses teeth in the back will reduce the chewing function, which results in digestive problems because the food that is chewed is not smooth and it can be said that, if a person gets older, it becomes more challenging to adapt to dentures (Pratiwi and Suhanda, 2009;Falatehan and Kusumah, 2018. Based on research conducted in the Jaya Baru area of Aceh, 181 people (67.0%) knew dentures in the excellent category, 65 people (24.1%) had the medium category, and 24 people (8.95) had a level of knowledge in the bad category (Chairunnisa et al, 2017). Based on the results of the bivariate test between education level and level of knowledge about wearing dentures, it was found that the majority of respondents with education level at elementary school (SD/MI), as many as 38 people (92.7%) stated that they had a good level of knowledge about using dentures.…”
Section: Discussionmentioning
confidence: 99%
“…This study's results align with Shigli et al (2007) where people are more motivated to use dentures to restore chewing than for esthetics and speech function. Because someone who loses teeth in the front will feel insecure in their environment, whereas someone who loses teeth in the back will reduce the chewing function, which results in digestive problems because the food that is chewed is not smooth and it can be said that, if a person gets older, it becomes more challenging to adapt to dentures (Pratiwi and Suhanda, 2009;Falatehan and Kusumah, 2018. Based on research conducted in the Jaya Baru area of Aceh, 181 people (67.0%) knew dentures in the excellent category, 65 people (24.1%) had the medium category, and 24 people (8.95) had a level of knowledge in the bad category (Chairunnisa et al, 2017). Based on the results of the bivariate test between education level and level of knowledge about wearing dentures, it was found that the majority of respondents with education level at elementary school (SD/MI), as many as 38 people (92.7%) stated that they had a good level of knowledge about using dentures.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, when HA material is combined with GIC fillers, it can impact the mechanical characteristics of the repair material. 22 The FS strength value is subject to variation based on several factors inside the test, such as the amount of variables involved, including manipulation methods, particle size, GIC types, and specimen sizes. Hence, challenges arise when attempting to establish a standardized measure for the mechanical strength of GICs.…”
Section: Discussionmentioning
confidence: 99%
“…Teeth loss is a dental and oral problem that often occurs mainly due to age. 1,2 Loss of teeth caused discomfort that could interfere in various daily life aspects such as talking, eating, socialization and self-confidence. 3 According to Basic Health Research (Riskesdas/ Riset Kesehatan Dasar) of the Ministry of Health of Indonesia in 2018, the prevalence of the Indonesian population who experienced the loss of all their teeth was 1.3%.…”
Section: Introductionmentioning
confidence: 99%
“…4 The loss of all teeth can be corrected by using prosthodontic treatment of making complete dentures to restore the function of the oral cavity and the level of confidence in daily activities. 2,5,6 The success of the complete denture treatment must be preceded by several procedures, one of them is determining the Vertical Dimension of Occlusion (VDO). VDO is the vertical relation between the maxilla and the mandible at centric occlusion.…”
Section: Introductionmentioning
confidence: 99%